1991
DOI: 10.1016/0022-2836(91)90595-w
|View full text |Cite
|
Sign up to set email alerts
|

Complementary recognition in condensed DNA: Accelerated DNA renaturation

Abstract: The functional consequences of DNA condensation are investigated. The recognition of complementary strands is profoundly modified by this critical phenomenon.(1) Condensation of denatured DNA greatly accelerates the kinetics of DNA renaturation. We propose a unifying explanation for the effects of several accelerating solvents studied here including polymers, di-and multivalent cations, as well as effects seen with the phenol emulsions and single-stranded nucleic acid binding proteins. Optimal conditions for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 61 publications
5
81
1
Order By: Relevance
“…Presumably, such coaggregates, held together by transient protein-protein, protein-DNA, and DNA-DNA interactions, act to reduce the sampling volume. An increase in the effective DNA concentration has indeed been shown to accelerate DNA catenation (28) and renaturation processes (29).…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, such coaggregates, held together by transient protein-protein, protein-DNA, and DNA-DNA interactions, act to reduce the sampling volume. An increase in the effective DNA concentration has indeed been shown to accelerate DNA catenation (28) and renaturation processes (29).…”
Section: Discussionmentioning
confidence: 99%
“…Krasnow and Cozzarelli [17] found virtually an absolute dependence of the rates of enzymatic DNA catenation on polyamine-induced DNA aggregation. In a comprehensive experimental and theoretical study of DNA condensation, Sikorav and Church [41] demonstrated 10-100-fold increases in reaction rates in DNA renaturation reactions under several condensing conditions, including condensation by crowding. Similarly large increases in cohesion rates between sticky-ended DNA fragments occur under condensing conditions [3].…”
Section: Reaction Rates Involving Dnamentioning
confidence: 99%
“…[31][32][33][34][35][36] DNA is also soluble in the presence of molecular solvents such as ethanol, dimethyl sulfoxide (DMSO), dimethylformamide (DMF) and acetonitrile (ACN), which can significantly accelerate DNA hybridization. [37][38][39][40] At the same time, these molecular solvents contain hydrophobic groups that can solvate the DNA bases and reduce DNA duplex stability. As a solvent, ILs are unique in many aspects.…”
Section: Introductionmentioning
confidence: 99%